Development and Characterization of Liquisolid Compact to Improve Dissolution of an Antihypertensive Drug - Kaur, Arvinder; Verma, Sachin; Paramesh, Deepa Bagur; Mahammad, Nawaz (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The goal of the current research was to use the straight forward, scalable, and economical Liquisolid compact to improve the dissolution profile of the poorly soluble medication Ramipril. Objectives: Utilising various polymers and liquid vehicles, the study's objective was to develop and characterise Liquisolid compact. Materials and Methods: Ramipril liquisolid were formulated using Propylene glycol and PEG 400 as liquid vehicle, MCC as a carrier, Aerosil 200 as a coating material. By using differential scanning calorimetry, the crystallinity of the newly developed drug formulation and the interactions between excipients were investigated. No interaction between the medication and excipients was established by FTIR tests. Results: The friability, hardness, weight variation, disintegration test, and in vitro dissolution investigations of all formed systems were evaluated for post-compression parameters. The optimized F9 formulation showed better results in vitro dissolution of 97.91% at 60 min, when compared with the marketed which showed 77.28% at 60 min. Conclusion: The drug release rates from liquisolid compacts were substantially higher than those from commercial formulations, which points to a potential strategy for speeding up the breakdown of medications that aren't very water-soluble.
Keywords: Ramipril; Liquisolid; Dissolution enhancement; Immediate drug release; FT-IR